2021
DOI: 10.1177/1553350620984650
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomical and Biomechanical Superiority of Novel Posterior En Bloc Elevation Cervical Laminoplasty

Abstract: Objectives. In this study, we performed a novel type of posterior en bloc elevation cervical laminoplasty (PEEL) to keep the integrity of the posterior structure, aiming to reduce axial symptoms complicated by a conventional cervical laminoplasty procedure. Methods. Twelve human cervical cadaveric spines (C2-T1) were sequentially tested in the following order: intact condition, open-door laminoplasty (ODL) through bilateral intermuscular approach (mini-invasive ODL), PEEL, and laminectomy (LN). After bilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Subramaniam et al [ 41 ] noted, using cadavers, the advantage of LP over LE in maintaining spinal stability: ROM after LE was 13% greater than after LP. Despite ample evidence from biomechanical studies [ 42 ], including those using computer modeling and finite element analysis [ 43 ], the results of the clinical use of LP in PSCT surgery remain uncertain. This may be because of the wide variety of LP techniques in PSCT surgery, which is supported by the data from published studies included in our systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…Subramaniam et al [ 41 ] noted, using cadavers, the advantage of LP over LE in maintaining spinal stability: ROM after LE was 13% greater than after LP. Despite ample evidence from biomechanical studies [ 42 ], including those using computer modeling and finite element analysis [ 43 ], the results of the clinical use of LP in PSCT surgery remain uncertain. This may be because of the wide variety of LP techniques in PSCT surgery, which is supported by the data from published studies included in our systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…The biomechanical effects of cervical laminectomy and/or foraminotomy have always been of interest. However, it has been argued that previous cadaveric studies may not represent the biomechanics of found in clinical practice as they mostly utilized cervical specimens denuded of posterior musculature [22]. Xie et al [23] reported that when the posterior ligament complex is intact, the removal of even 50% of the facet joints does not lead to signi cant changes in cervical spine stability and mobility.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Franch door laminoplasty (also known as double-door expansive laminoplasty) is another modified procedure of laminoplasty, which can achieve symmetric decompression by separating the bilateral laminae from the midline of the spinous process and lift the laminae from the spinal cord. Additionally, to minimize the intraoperative attached ligament cut-off and extensor muscle detachment and following axial pain and malalignment of the cervical spine, many modified laminoplasty procedures have been developed, such as skip laminoplasty [89], en bloc elevation cervical laminoplasty [90], and the posterior muscle-ligament complex preserving modified unilateral laminoplasty [91]. These modified procedures are designed to preserve the deep extensor attachment, preserve the spinous process attachment of C2 and/or C7, or skip the level to minimize surgical injury.…”
Section: Laminoplastymentioning
confidence: 99%